A catalog of spectroscopic binary candidate stars derived from a comparison of Gaia DR2 with other radial velocity catalogs. Issue 5 (19th June 2019) - Jack, Dennis
Abstract: Using the recently published Gaia second data release that includes measurements of the mean radial velocity of about 7.2 million stars, we performed a systematic comparison with other existing radial velocity catalogs to search for variations in the radial velocity measurements, with the goal that detected differences may indicate that these stars are possibly spectroscopic binary stars with only one visible component (SB1). We present a catalog of spectroscopic binary candidate stars containing 35, 246 stars, compiled to encourage follow‐up observations obtaining spectra at different epochs of orbits of these stars to verify their binarity and to study these systems using radial velocity curves. Comparing the Gaia DR2 database with the K‐M dwarf catalog, we found 16 stars that show radial velocity variations. In a comparison with the Pulkovo radial velocity catalog of Hipparcos stars, we identified a total of 539 SB1 candidate stars. In the largest radial velocity catalog available, the radial velocity experiment (RAVE) catalog, we found a total of 34, 691 stars that show radial velocity variations when compared to the Gaia DR2 data.